2021
DOI: 10.1016/j.jviromet.2021.114122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two commercial surrogate ELISAs to detect a neutralising antibody response to SARS-CoV-2

Abstract: Introduction Reliable methods for the detection of SARS-CoV-2 neutralising antibodies (NAbs) are essential for the evaluation of vaccine candidates and for the selection of convalescent plasma donors. Virus neutralisation tests (NTs) are the gold standard for the detection and quantification of NAbs, but they are complex and require BSL3 facilities. In contrast, surrogate enzyme-linked immunosorbent assays (sELISA) offer the possibility of high-throughput testing under standard laboratory safety c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
3
30
1
Order By: Relevance
“…Using the DiaSorin “Liaison SARS-CoV-2 S1/S2 IgG assay” ( Krüttgen et al, 2021 ) and a surrogate virus neutralization assay (“TECO SARS-CoV-2 Neutralization Antibody Assay”, TECOmedical) ( Müller et al, 2021 ), we confirmed that all vaccinees (18/18) in our study had successfully mounted humoral immune responses after mRNA-1273 vaccination (data not shown). We also tested our vaccinees for anti-Nucleocapsid IgG (“recomWell SARS-CoV-2 IgG ELISA” from Microgen) which is a marker for past covid-infections.…”
Section: Resultssupporting
confidence: 64%
“…Using the DiaSorin “Liaison SARS-CoV-2 S1/S2 IgG assay” ( Krüttgen et al, 2021 ) and a surrogate virus neutralization assay (“TECO SARS-CoV-2 Neutralization Antibody Assay”, TECOmedical) ( Müller et al, 2021 ), we confirmed that all vaccinees (18/18) in our study had successfully mounted humoral immune responses after mRNA-1273 vaccination (data not shown). We also tested our vaccinees for anti-Nucleocapsid IgG (“recomWell SARS-CoV-2 IgG ELISA” from Microgen) which is a marker for past covid-infections.…”
Section: Resultssupporting
confidence: 64%
“…This result differs from the results of a recently published study by Müller K et. al., in which only 68.7% (158/230) of these IgG positive samples were also positive in NTs [17]. This paper uses ELISA method to detect COVID-19 antibody, which is different from chemiluminescence method used in our paper.…”
Section: Discussionmentioning
confidence: 97%
“…Of the surrogate ELISAs examined in our study, the GenScript assay demonstrated the highest sensitivity of 100% and a specificity of 87%, which is comparable to data from other studies. In the literature, also, testing clinical specimens and when the PRNT is used as the reference method, sensitivity ranges from 77 to 100% and specificity ranges from 69.5 to 100% [ 15 , 26 , 27 , 28 ]. When serum follow-up samples taken >14 days after rRT-PCR positivity were analyzed, the GenScript assay demonstrated a sensitivity of 97.3% and a specificity of 99.4% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These assays work according to the principle of competitive binding: anti-SARS-CoV-2 neutralizing antibodies block an enzyme-labeled S-RBD protein from binding its natural ligand, the angiotensin-converting enzyme 2 (ACE2), pre-coated on a microtiter plate. Surrogate ELISAs are high-throughput capable and can be performed under standard laboratory safety conditions [ 15 , 16 ]. However, there are limited data on their performance when testing specimens of individuals with past SARS-CoV-2 infection or follow-up samples of SARS-CoV-2 vaccinated individuals and especially how they compare to the PRNT.…”
Section: Introductionmentioning
confidence: 99%